Methodological approach to assessing the competitiveness of the region's manufacturing sector - Khmeleva Galina; Skreblov Nikita (π-Economy)
The relevance of the article lies in the need to increase the level of global competitiveness of Russian regions. Russia is facing the challenge of advanced development in order to move from import substitution to the expansion of non-resource non-energy exports. This means that it is necessary to move away from understanding competitiveness as a competition between regions. In modern conditions, the competitive economy of the region means the ability to provide domestic and foreign markets with products from manufacturing industries. This aspect requires a revision of the usual methods of assessing the competitiveness of the regional economy towards shifting the focus to understanding changes in the localization of manufacturing industries and the export specialization of the region. The objective of the study is to develop a methodological approach to assessing the competitiveness of manufacturing sector from the perspective of regional trade opportunities in global markets. The main hypothesis of the study is the assumption that the level of competitiveness and the use of competitive advantages of the region is characterized by the degree of localization, comparative advantages and export specialization. To achieve the objective of the study, the paper presents a methodological approach that includes three stages: an assessment of the localization index by types of economic activity in the manufacturing industry, an assessment of the comparative advantages and export specialization of the region for certain types of products, and the development of a typology based on changes in localization and export of products. The peculiarity and novelty of the proposed methodological approach is to take into account not only changes in the localization of industry, but also the export of certain types of products manufactured by enterprises localized in the region. This approach can be extended to other types of economic activity. In addition, the degree of detail can be increased according to the commodity nomenclature of foreign economic activity. The results of the study made it possible to confirm the decrease in the level of technological dependence in the regions, since, compared to others, the geography of specializations in the production of electronic equipment and mechanical engineering is expanding at the fastest pace. The pattern is confirmed that regions with a higher level of specialization are more successful in exports than the national average. It has been revealed that regions with relatively small production and export scales can still be more competitive in foreign markets and less dependent on imports than regions with large production facilities, since they use the existing industrial potential more fully and effectively. The proposed methodological approach allowed us to offer recommendations on strengthening competitiveness for each of the four types of regions. The advantages and novelty of the proposed methodological approach lie in the most complete assessment of the region's use of competitive advantages in the global market. The theoretical value lies in identifying the actualization of the methodological apparatus for assessing regional competitiveness. The practical value lies in the possibility of using the results obtained for management decisions on the development of specialization in the regions and the development of support measures to ensure technological sovereignty. The directions of further research are related to detailing the product groups in which regions can increase the level of competitiveness and to expanding the geography of exports.